The β‐domain of streptokinase affects several functionalities, including specific/proteolytic activity kinetics - Maryam Rafipour; Malihe Keramati; Mohammad Mehdi Aslani; Arash Arashkia; Farzin Roohvand (FEBS Open Bio, 2019)
Streptokinase (SK) is a plasminogen activator which converts inactive plasminogen (Pg) to active plasmin (Pm), which cleaves fibrin clots. SK secreted by groups A, C, and G Streptococcus (SKA/SKC/SKG) is composed of three domains: SKα, SKβ and SKγ. Previous domain‐swapping studies between SK1/SK2b‐cluster variants revealed that SKβ plays a major role in the activation of human Pg. Here, we carried out domain‐swapping between skcg‐SK/SK2‐cluster variants to determine the involvement of SKβ in several SK functionalities, including specific/proteolytic activity kinetics, fibrinogen‐bound Pg activation and α2‐antiplasmin resistance. Our results indicate that SKβ has a minor to determining role in these diverse functionalities for skcg‐SK and SK2b variants, which might potentially be accompanied by few critical residues acting as hot spots. Our findings enhance our understanding of the roles of SKβ and hot spots in different functional characteristics of SK clusters and may aid in the engineering of fibrin‐specific variants of SK for breaking down blood clots with potentially higher efficacy and safety.